Simple and efficient Fmoc removal in ionic liquid. Issue 58 (21st July 2017) - Di Gioia, M. L.; Costanzo, P.; De Nino, A.; Maiuolo, L.; Nardi, M.; Olivito, F.; Procopio, A.
Abstract : The combination of triethylamine and [Bmim][BF4 ] represents a mild method for efficient removal of the Fmoc group. Abstract : A mild method for an efficient removal of the fluorenylmethoxycarbonyl (Fmoc) group in ionic liquid was developed. The combination of a weak base such as triethylamine and [Bmim][BF4 ] makes the entire system more efficient for the cleavage at room temperature of various amines and amino acid methyl esters in short reaction times. The procedure works well even in the case of N -Fmoc amino acids bearing acid-sensitive protecting groups and of N -alkylated amino acid methyl esters. The solvent-free condition provides a complementary method for Fmoc deprotection in solution phase peptide synthesis and modern organic synthesis.